Electro-analytical performance of bifunctional electrocatalyst materials in unitized regenerative fuel cell system. (27th September 2018) - Sadhasivam, T.; Palanisamy, Gowthami; Roh, Sung-Hee; Kurkuri, Mahaveer D.; Kim, Sang Chai; Jung, Ho-Young
Abstract: The unitized regenerative fuel cell (URFC) is a round-trip energy conversion device for efficient energy storage systems that offers promising electrochemical energy conversion and environmentally friendly features. The electrocatalyst is a key component for operating URFC unit cell devices. Optimal electrocatalyst materials should be bi-functional with catalytic activity for the oxygen reduction and oxygen evolution reactions (ORR and OER). Over the past few decades, platinum has been recognized as a promising bi-functional electrocatalyst material for the URFC system. However, the ORR and OER activity of Pt is inadequate during the round-trip energy conversion process due to the formation of an oxide layer (PtOx ) and the high onset potential for H2 evolution. To address these issues, extensive effort has been made to enhance the OER performance without affecting the ORR performance. The most efficient alternative electrocatalyst materials comprise combinations of platinum group metals (PGMs) and their oxides, especially PtIr, PtIrRu, PtIrO2, PtIrIrO2, and PtIrO2 RuO2 . This comprehensive review emphasizes the potential of various bifunctional electrocatalyst materials for renewable energy generation in the URFC system. Herein, we discuss the limitations of Pt electrocatalysts in the URFC-OER process based on the reaction mechanism. The classification of different bifunctional electrocatalysts is extensively reviewed and highlighted based on the structural, microstructural, fuel cell-ORR, and water electrolysis-OER characteristics, round-trip energy conversion efficiency, inadequacies, and advantages. Taking these features into account, we discuss the possibilities and performance of cost-effective bifunctional electrocatalyst materials for the ORR/OER electro-catalytic process in advanced URFC systems. This review presents an exclusive vision for the development of bifunctional electrocatalyst materials and should stimulate research on bifunctional electrode-based URFC systems. Highlights: URFC is an efficient round-trip energy conversion device with high specific energy. Bifunctional electrocatalyst is a key component for operating URFC unit cell. Pt suffered by formation of PtOx layer and high onset potential for H2 evolution. Pt/IrO2 is superior electrocatalyst material for efficient ORR/OER performances. Cost-effective and novel structured electrocatalysts are an alternative to PGM.